Routledge handbook of the contemporary Philippines - Thompson, Mark R. 1960-; Batalla, Eric C. (Routledge Taylor & Francis Group, 2018)
"The Philippines is a fascinating example of a 'poor country democracy' where issues of economic development and poverty, political participation and stability as well as ethnicity and migration are crucial. The Routledge Handbook of Contemporary Philippines provides a comprehensive overview of the current political, economic, social and cultural issues of the country. The Handbook is divided into the following four sections concentrating on a different aspect of the Philippines: Domestic politics, Foreign relations, Economics and social policy, Cultures and movements. Chapters discuss the political parties and contested elections, as well as dynasties and local governance in the Politics section, and the Economics section looks at topics such as international political economy, industrial policy and economic nationalism. The section on Philippine society highlights the women's movement and gender issues, and goes on to concentrate on religion, culture and customs. The Philippines is confronted with many foreign challenges, and the final section focuses on the relationship the country has with China, Japan, Europe and the USA. Written by leading experts in the field, the Handbook provides students, scholars and policymakers of Southeast Asia with an interdisciplinary resource on the evolving politics, society and economics of the Philippines"-- Provided by publisher.